Design and Implementation of the SALUTS System to Support of Improvement of Tourism Transactions and Promotion - Akhir Putra, Juniardi; Nuryadi, Halid; Yuliadi, Yuliadi; Mardinata, Erwin; Hudaya, Chairul; Esabella, Shinta; Putra, Ardiansyah; Juliansyah, Ahmad (Brilliance: Research of Artificial Intelligence, 2023)
This research aims to design and build a tourism system in Sumbawa Regency. In this research is using a qualitative approach that used model of rapid application development (RAD) for system development life circle (SDLC) method. Overall the first stage is system planning, next stage is analyzing tourism data and information that would be presented on web and android technology based. In addition, for users interface display is the attractive database design. The final stage is coding the system and produce a prototype for the implementation which is presenting on the web pages and google play store for android smartphones. The system presented could be used for evaluation, monitoring and facilitating of tourism transaction and promotion processes in Sumbawa Regency.